Elimination of CM Noise from SMPS Circuit using EMI Filter - Venkata Sai Charishma Pathala; Pappu, V.Y. Jayasree (International Journal of Electrical and Computer Engineering Systems, 2023)
The electronic devices are exposed to external electromagnetic signals that produce an unwanted signal called noise in the circuit, which causes electromagnetic interference [EMI] problems. It occurs in two modes: radiated mode and conducted mode. In the radiation mode, the shielding technique is used for radiation mode, in conduction mode filtering technique is used. The design of an EMI filter depends upon the type of noise generated by the Switched Mode Power supply circuit [SMPS]. The SMPS circuit used in this paper is a DC-DC power converter, the Boost converter is a step-up converter and Buck converter is step down converter are considered as equipment for generation of noise, the Line Impedance Stabilization Network [LISN]is used for generating the common output impedance to the power converters, the EMI filters are designed to eliminate noise generated by the circuits. There noise generated by this power converters is Common Mode [CM] noise and Differential Mode [DM] noise. The separation of noise from the equipment is done by using a noise separator. In this paper, CM noise generated by these power converters is eliminated by designing an EMI filter called an inductor filter and a PI filter. The comparison between the LC inductor filter and the PI filter for the boost and buck converters is observed. The PI filter has better performance characteristics when compared to the inductor filter for both SMPS circuits as per the Comité International Special des Perturbations Radioélectriques [CISPR] standards. This standard gives the conducted emission range for different electronic devices.